Natural and synthetic microfibers alter growth and behavior in early life stages of estuarine organisms - Siddiqui, S.; Hutton, S. J.; Dickens, J. M.; Pedersen, E. I.; Harper, S. L.; Brander, S. M. (Frontiers in Marine Science, 2023)
Increasing shares of microfibers are being detected in environmental samples and a closer look to identify the risk associated with them using ecologically relevant endpoints, especially at sensitive early life stages, is needed. To assess exposure hazards, we used rope samples representative of fiber types ubiquitous in coastal systems, where microfibers are often the most common debris type found in the water column. To compare responses to natural vs. synthetic microfibers, we used rinsed “natural” cotton, polyester, and polypropylene microfibers (80-150 µm length, 8-20 µm width) created from the rope. Larval and juvenile estuarine indicator species Inland Silverside (Menidia beryllina) and mysid shrimp (Americamysis bahia), respectively, were exposed to these three microfiber types at three concentrations (3, 10, 30 particles/ml) along a 5-25 PSU salinity gradient to mimic estuarine conditions. Behavioral responses, growth, and ingestion were measured. The cotton microfibers were not detected in the digestive tracts of Silversides, however, both the polyester and polypropylene microfibers were detected in the Silversides’ stomach and gut lining. None of the fiber types were detected in mysid shrimps. Mysids exposed to cotton microfibers had fewer behavioral effects compared to Silversides, who responded more to cotton. Cotton exerted no effect on growth in Silversides but did cause reduced growth in the mysids at the two lower salinities. In contrast, polyester and polypropylene were identified to have a significant dose dependent effect on mysid and Silverside behavior as well as growth was affected in at least one of the three salinities at concentrations as low as 3 particles/ml. Cotton impacted both the organism’s behavior more at higher salinities, whereas polyester and polypropylene had more impacts at lower salinities. This raises concerns for microfiber impacts on estuarine ecosystems and the need for policies to limit microfiber production and outfall into the aquatic environment.